Tuna luncheon meat manufacturing plant - Delos Santos, Odessa J.; Empamano, Imelda A.; Jimenez, Jacquiline Alma C.; Santos, Grace C. (Diliman, Quezon City College of Engineering, 1997)
Product: Tuna luncheon meat -- Plant location: Navotas, Metro Manila -- Total land area: 12,354 sq.ft. -- Annual volume of production at full plant capacity: 2,085,895 cans -- Net weight per can: 180 grams -- Annual gross sales: Php 72,770,179.00 -- Annual income: Php 15,584,336.00 -- Total Investment Cost: Php 24,117,027.00 -- Working capital: Php 4,823,405.00 -- Product Cost: Php 17.50 -- Product factory price: Php 28.00 -- Suggested retail price per can: Php 32.00 -- Return on investment: 64.62% -- Payback period: 1.2 years
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Tuna canning industry